Antibiotic collateral sensitivity is contingent on the repeatability of evolution - Daniel Nichol (Nature Portfolio, 2019)
The evolution of resistance to an antibiotic can render bacteria more susceptible, or more resistant, to a second antibiotic. Here, Nichol et al. provide evidence that the final outcome can be fairly stochastic and depends on the shape of the evolutionary fitness landscape.